2014
DOI: 10.1016/j.rboe.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional evaluation of forefoot reconstruction in patients with rheumatoid arthritis

Abstract: Objectiveto evaluate the long-term results from reconstruction of the forefoot in patients with rheumatoid arthritis who underwent arthrodesis of the metatarsophalangeal joint of the hallux, resection arthroplasty of the heads of the lateral metatarsals and correction of the deformities of the smaller toes through arthrodesis of the proximal interphalangeal joint or closed manipulation.Methodsseventeen patients (27 feet) who underwent forefoot reconstruction surgery by means of arthrodesis of the first metatar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Despite this positive effect on VAS scores, this improvement was not reflected in the quality-of-life pattern of the patients, contradicting partially the results described by Freire et al (2020) in which the application of plasma reduced pain and improved quality of life. Other studies (Costa, Backer & Ferreira, 2014, Andia, Sanchez & Maffulli, 2010 have also observed the progressive improvement of patients' quality of life via the AOFAS score over different evaluation times.…”
Section: Discussionmentioning
confidence: 85%
“…Despite this positive effect on VAS scores, this improvement was not reflected in the quality-of-life pattern of the patients, contradicting partially the results described by Freire et al (2020) in which the application of plasma reduced pain and improved quality of life. Other studies (Costa, Backer & Ferreira, 2014, Andia, Sanchez & Maffulli, 2010 have also observed the progressive improvement of patients' quality of life via the AOFAS score over different evaluation times.…”
Section: Discussionmentioning
confidence: 85%